Participation in Illegitimate Activities: Ehrlich Revisited, 1960 - Vandaele, Walter ([Verlag nicht ermittelbar], 1987)
This study re-analyzes Isaac Ehrlich's 1960 cross-section data on the relationship between aggregate levels of punishment and crime rates. It provides alternative model specifications and estimations. The study examined the deterrent effects of punishment on seven FBI index crimes: murder, rape, assault, larceny, robbery, burglary, and auto theft. Socio-economic variables include family income, percentage of families earning below half of the median income, unemployment rate for urban males in the age groups 14-24 and 35-39, labor force participation rate, educational level, percentage of young males and non-whites in the population, percentage of population in the SMSA, sex ratio, and place of occurrence. Two sanction variables are also included: 1) the probability of imprisonment, and 2) the average time served in prison when sentenced (severity of punishment). Also included are: per capita police expenditure for 1959 and 1960, and the crime rates for murder, rape, assault, larceny, robbery, burglary, and auto theft.